Undergraduate students’ performance and perception of video-recordings versus live demonstrations for teaching orthodontic laboratory procedures: a randomized trial - Serene A. Badran; Iyad Al-omari; Abdelrahman Shqaidef; Zaid Al-Bitar; Ahmad M. Hamdan (BMC Medical Education)
Abstract Objectives To compare three methods of delivering an orthodontic laboratory procedure on students’ academic performance; live demonstration, video-recorded demonstration, or both. To assess students’ perceptions and preferences to the demonstration methods employed. Materials and methods A total of 202 fourth-year undergraduate students were randomly allocated to three groups; live demonstration, video-recorded demonstration, or both. Students were instructed to construct a buccal canine retractor immediately after the demonstration method ended, answer 2 short essay questions about buccal canine retractors to assess their theoretical comprehension, and fill a questionnaire to assess their perception and attitude towards the methods of demonstration. Results The mean score for construction of the buccal canine retractor was significantly higher for the live demonstration group compared to the 2 other groups (P < 0.05). There were no significant differences between the 3 groups in answering the essay questions (P > 0.05). Most students (95.3%) agreed that live demonstrations helped them visualize and understand difficult wire bending techniques, and allowed interaction between students and the lecturer (93.9%). Around 83% agreed that video recordings were a useful aid to live demonstrations but only 11.9% indicated that they could totally replace live demonstrations. More than half of the students preferred a live demonstration compared to watching a video-recording. Conclusion The live demonstration group performed better than the video-recorded demonstration group. Most students preferred a live demonstration method of teaching orthodontic wire bending, however the majority indicated that a video-recorded demonstration was a useful aid to a live demonstration.